Mapuche ethnicity and vulnerability: a look from the indicators of socioeducational deficiency (Encuentros, 2020)
Mapuche communities have faced a persistent territorial and symbolic exclusion in the educational services that the State has provided for its national population. Therefore, this article analyzes the situation of socio-educational vulnerability that affects the population with Mapuche ancestry residing in the southern macrozone from a multidimensional perspective. The design is quantitative, descriptive and transversal. The results show that the Mapuche population has higher levels of rurality and poverty. Among the indicators of multidimensional poverty, Schooling and Environment showed the highest prevalence. In terms of educational quality, Mapuche students achieve lower scores on standardized SIMCE tests and mostly attend municipal educational establishments that serve vulnerable populations. Moreover, they share classroom with low-performing students and curricular proficiency. The conclusions indicate the need to resolve existing cultural differences and educational gaps to generate a more inclusive educational system with the indigenous population and that provides equal opportunities for access, permanence and quality.